Posturografia do Balance Rehabilitation Unit (BRUTM) na doença de Menière - Cusin, Flávia Salvaterra [UNIFESP] (2009)
Purpose: To evaluate balance control with posturography by Balance Rehabilitation Unit (BRU™) in patients with Menière’s disease. Method: A cross controlled study was performed including 30 patients diagnosed as definete Menière’s disease and a control group consisting of 40 healthy individuals, matched by age and gender. Patients were submitted to a balance function evaluation, by means of Balance Rehabilitation Unit (BRU™) posturography. Results: In the comparison of patients with Menière’s disease and the control group occured significant differences between the mean values of the sway speed in the conditions static force plate and down optokinetic stimulation (p=0,038) and static force plate and visual vestibular interaction with horizontal bars stimulation (p=0,049); and of the ellipse area in the conditions static force plate and closed eyes (p=0,001); static force plate and left optokinetic stimulation (p=0,007); static force plate and down optokinetic stimulation (p=0,003); static force plate and visual vestibular interaction with horizontal bars stimulation (p=0,003); and static force plate and visual vestibular interaction with vertical bars stimulation (p=0,028). Conclusion: The postural control assessment with posturography by the Balance Rehabilitation Unit (BRU™) enables the identification of sway speed and ellipse area abnormalities in patients with Menière’s disease.